Perspektif Perkembangan Pariwisata Di Desa Huta Sialagan Kabupaten Samosir Dalam Mendukung Keberadaan Kaldera Toba - Akmal, Rifki; Tauhid, Booni; Chaidir, Muhammad; Yusrapida, Novi; Marpaung, Ronald; Rambe, Mukmin (Jurnal Akademi Pariwisata Medan, 2025)
This research aims to examine the perspective of tourism development in Huta Sialagan Village, Samosir Regency, in supporting the existence of the Toba Caldera as part of the UNESCO Global Geopark. Using a descriptive qualitative approach through the library research method, this research explores the concepts, principles, and application of geotourism based on four main aspects: tourism, accommodation, interpretation, and planning management. The results of the study show that the geotourism potential in this village is very large, especially from the cultural and historical aspects, but has not been fully integrated with the geological narrative of the Toba Caldera. The lack of interpretive media, limited eco-friendly accommodation, and the absence of geotourism-based zoning are the main challenges. The research also found that community participation, business involvement, and support from related agencies still need to be strengthened through training, digital promotion strategies, and integrated planning based on geopark principles. Therefore, the development of geotourism in Huta Sialagan Village requires cross-sector collaboration and a sustainable approach to support the preservation of the Toba Caldera while improving the welfare of local communities.